2023
DOI: 10.3390/nu15173711
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Breakfast Fat Composition Can Modulate Cytokine and Other Inflammatory Mediators in Women: A Randomized Crossover Trial

Jessica M. Delgado-Alarcón,
Juan José Hernández Morante,
Juana M. Morillas-Ruiz

Abstract: Previous trials have demonstrated that modifying dietary fat composition can influence the production of inflammation-related factors. Additionally, it has been suggested that not only the type of fat, but also the timing of fat intake can impact these factors. Therefore, the objective of the present study was to evaluate the effect of altering breakfast fat composition on inflammatory parameters. A 3-month crossover randomized trial was designed, involving 60 institutionalized women who alternately consumed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…There is a large quantity of studies that have previously evaluated the impact of dietary fat on human health [4][5][6]; however, the works of this issue confirm that there is still much to learn about the effect of consuming fat on health. The work of Delgado-Alarcón also demonstrated the relevance of breakfast on human health maintenance [7]. Concretely, this work highlighted the fact that a single modification of fat eaten at breakfast was enough to improve the inflammation profile of women.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…There is a large quantity of studies that have previously evaluated the impact of dietary fat on human health [4][5][6]; however, the works of this issue confirm that there is still much to learn about the effect of consuming fat on health. The work of Delgado-Alarcón also demonstrated the relevance of breakfast on human health maintenance [7]. Concretely, this work highlighted the fact that a single modification of fat eaten at breakfast was enough to improve the inflammation profile of women.…”
mentioning
confidence: 72%
“…This randomized trial evaluated the influence of monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFAs) and saturated fatty acids (SFAs) on a cluster of cytokines and other inflammation markers. The results obtained by Delgado-Alarcón et al demonstrated that a MUFA-enriched breakfast was the best option for decreasing the synthesis of these markers, an effect that was especially evident for interleukin-6 (Il-6) and vascular/endothelial growth factor (VEGF) [7]. The other work that evaluated the effect of fat on human health was the study conducted by Portela et al [8].…”
mentioning
confidence: 99%